(3GdJMaI GdHcQjI aj CMcGe GdESJMeGe GdcdjI hGdLRFjIs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s
(3ChdgG (B:s
(3jGef ZeS bdhH GdYGQajf ai HMGQ GdCFI hHYO adeG bU GdUGOQ GdChd hGSJHO Pdc YfO ef Ydjg bhd s
(3BNQgG (B:s
(3hjWHN Gdcd MJi jHbi GdfUa Ke jVGa Edjg eKdg ScQ fbi hjSjQ ef GdRYaQGf hjWHN MJi jfYbO hgPG JeGe eG ChQOfGg s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGfjIs
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs